The Role of Personal Responsibility and Career Planning among Adolescents in Indonesia: A Correlational Study - Handaka, Irvan; Wirawati, Denik; Setyowati, Aprilia; Saputra, Wahyu Nanda Eka; Herdiansyah, Diki; Triskova, Navy Glenda; Septikasari, Zela; Kawai, Norimune; Jaladin, Rafidah Aga Mohd (citeus, 2025)
Personal responsibility is an individual's ability to identify and regulate one's thoughts, feelings, and behaviors and the willingness to take responsibility for the choices and resulting social and personal outcomes. Through a quantitative correlational study, this study explores the role of personal responsibility and career planning in high school students/adolescents. A total of 465 adolescent subjects from Indonesia were sampled in this study. The data collection method used instruments tested for validity and reliability in measuring personal responsibility and career planning. Data analysis was conducted using descriptive statistics to describe the level of personal responsibility and career planning and inferential statistics, namely product moment and simple linear regression, to test the relationship between the two variables. The results showed that 50.9% of students showed that the level of personal responsibility was high, while 60.8% indicated that career planning was medium. Statistical analysis also shows a positive and significant relationship between personal responsibility and career planning, with a practical contribution of 88.1%, while other factors influence the rest. The implications of this study can be the basis for school counselors to help develop students' career planning skills. This study also encourages further researchers to use the study results as a basis for providing guidance and counseling service interventions, especially related to personal responsibility and career planning.